The Matrix in theory - Díaz-Diocaretz, Myriam; Herbrechter, Stefan (Critical studies (Amsterdam, Netherlands), 2006)
The Matrix trilogy continues to split opinions widely, polarising the downright dismissive and the wildly enthusiastic. Nevertheless, it has been fully embraced as a rich source of theoretical and cultural references. The contributions in this volume probe the effects the Matrix trilogy continues to provoke and evaluate how or to what extent they coincide with certain developments within critical and cultural theory. Is the enthusiastic philosophising and theorising spurred by the Matrix a sign of the desperate state theory is in, in the sense of "see how low theory (or 'post-theory') has sunk.